Exploring Junior High Students’ Perceptions and Barriers in Implementing the Flipped Classroom Model for Mathematics in Ghana - Twum, Derrick; Ofori Nyarko, Addision; Martey, Yvonne; Twum Pobi, Philip; Adukpoh, Richard; Donkoh, Gabriel; Ahiamanyoh Mawuli, Richmond (International Journal of Mathematics and Mathematics Education (IJMME), 2025)
Purpose – The flipped classroom model is increasingly recognized as an innovative approach to enhance student engagement and understanding in mathematics education. However, its implementation and effectiveness in low-resource settings, such as Ghana, remain underexplored. This study investigates junior high school students’ perceptions of and challenges with the flipped classroom model in the context of mathematics instruction. Methodology – A descriptive survey design was employed involving 31 junior high school students in Ghana. Data were collected using a structured questionnaire that assessed students’ experiences, perceptions, and barriers associated with the flipped learning approach. Findings – The results showed generally positive perceptions of the model. A total of 61.3% of students agreed that pre-class videos enhanced conceptual understanding, while 83.9% reported increased engagement during in-class activities. Nonetheless, substantial challenges were identified, including data exhaustion (51.6%) and lack of access to personal digital devices (58.1%), which limited students’ ability to fully engage with pre-class materials. Novelty – This study offers a unique contribution by examining the flipped classroom model in a low-income educational context. Unlike previous research focused on high-resource environments, this study addresses the practical realities of digital inequality and provides learner-centered insights into adapting flipped learning in under-resourced settings. Significance – The findings highlight the potential of flipped learning in improving mathematics instruction, while also underscoring the infrastructural and technological barriers that must be addressed. These insights can guide educators and policymakers in designing inclusive, context-appropriate strategies for effective technology integration in education.